Low-Level HIV RNA in Cerebrospinal Fluid and Neurocognitive Performance: A Longitudinal Cohort Study. (15th August 2021) - Anderson, Albert M.; Tang, Bin; Vaida, Florin; Mcclernon, Daniel; Deutsch, Reena; Cherner, Mariana; Cookson, Debra; Crescini, Melanie; Grant, Igor; Ellis, Ronald J.; Letendre, Scott L.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Cognitive complications persist in persons with HIV during suppressive antiretroviral therapy (ART). Low levels of HIV during ART could contribute to these complications. In this study, we measured cerebrospinal fluid (CSF) HIV using a single-copy assay (SCA) to investigate a possible relationship between low-level HIV and cognition. Design/Methods: SCA data were analyzed from 3 consecutively paired CSF–plasma specimens collected over a mean of 456 days from 96 participants on suppressive ART. Using mixed models, the presence of CSF HIV by SCA as a risk factor for worse neurocognitive performance was examined. Results: At baseline on the SCA, 45.8% of participants had detectable plasma HIV RNA (median 8 copies/mL and interquartile range = 3–17 among detectable values) and 17.7% had detectable CSF HIV RNA (median CSF concentration= 3 copies/mL and interquartile range= 2–13 among detectable values). The frequency of CSF HIV RNA detection declined over time in CSF ( P = 0.018) with a trend toward decline in plasma ( P = 0.064). Detectable CSF HIV RNA during the study was associated with worse performance in the domains of recall ( P = 0.014) and motor ( P = 0.040) and a trend with worse overall global performance ( P = 0.078). Integrase inhibitor use, although very infrequent in this cohort, was associated with better performance in 2 domains. Conclusions: Low-level CSF HIV RNA declines with time but is associated with worse cognitive performance in 2 domains. Additional research is needed to better understand the relationship between HIV RNA persistence during long-term ART and central nervous system complications in persons with HIV.